SISTEM PENDUKUNG KEPUTUSAN PEREKRUTAN OPERATOR MESIN COMPUTER NUMERICAL CONTROL DENGAN METODE WEIGHTED PRODUCT - Achmad Udin Zailani; Ari Irawan (Universitas Bunda Mulia, 2018)
The CNC (Computer Numerical Control) machine is an automated system operated by abstart-programmed commands on a computer. CNC machines must be operated by a competent operator. The purpose of this research is to make a decision support system of recruitment of CNC machine operator. The method used is weighted product method. The weighted product method uses multiplication to attribute the attribute rating, where each attribute must be raised first with the attribute weights. This research has successfully applied the weighted product method in PT.Jatibaru Mandiri for recruitment of CNC machine operators so that recruitment is more objective and makes the recruitment system of CNC machine operator become more accurate..Keywords: Recruitment Operators, CNC Machines, Weighted Product Methods